Clinical Factors Affecting Condition-Specific Quality-of-Life Domains in Pediatric Patients after Repair of Esophageal Atresia: The Swedish-German EA-QOL Study - Dellenmark-Blom, Michaela; Quitmann, Julia; Dingemann, Jens; Witt, Stefanie; Ure, Benno M.; Bullinger, Monika; Jönsson, Linus; Gatzinsky, Vladimir; Dingemann, Carmen (European Journal of Pediatric Surgery, 2020)
Introduction We aimed to identify clinical factors affecting condition-specific health related quality of life (HRQOL) domains in children born with esophageal atresia (EA). This can facilitate preventive care to risk groups of HRQOL impairments.Materials and Methods A total of 124 Swedish and German families of EA children answered the validated EA-QOL questionnaires (response rate 68%), for evaluation of three HRQOL domains in children 2 to 7 years old (53 parents) and four HRQOL domains in children 8 to 17 years old (62 children/71 parents). Clinical data were collected through medical records and a questionnaire. Statistics included between—group analysis, univariable and stepwise multivariable regression analysis, p < 0.05.Results Between 2 to 7 years, no primary anastomosis (p = 0.022) and female gender (p = 0.026) predicted worse scores related to “physical health and treatment,” and gastrostomy insertion related to “eating” (p = 0.0001), and “social isolation and stress” (p = 0.001). Between 8 to 17 years, no primary anastomosis (child report), prematurity, esophageal dilatation (parent report) predicted poor HRQOL related to “eating” (p < 0.05), associated anomalies to “body perception” (p = 0.031, parent report), female gender (p = 0.018, child report) and severe EA (p = 0.011 child report, p = 0.004 parent report) to “social relationships,” and severe EA predicted worse “health and well-being” scores (p = 0.004, parent report). An increased number of digestive symptoms (difficulty swallowing food, heartburn, and vomiting), lowered all EA-QOL domain scores in both age groups (p < 0.001). An increased number of respiratory problems (cough, wheezing, airway infections. breathlessness, and chest tightness), lowered scores in two HRQOL domains among children 2 to 7 years (p < 0.05).Conclusion Impairments within condition-specific HRQOL domains in EA children are found in congenital and surgical subgroups, and notably related to digestive symptoms throughout childhood.
Keywords: esophageal atresia; quality of life; health-related quality of life; pediatric surgery; children